STRUCTURAL CHARACTERIZATION OF LOCAL PRODUCTIVE ARRANGEMENTS: AN APPLICATION IN THE MINERAL EXTRACTION SECTOR ON BRAZILIAN MICROREGION - Gonçalves, Anderson Tiago Peixoto; Cândido, Gesinaldo Ataíde (Contextus - Revista Contemporânea de Economia e Gestão, 2014)
This study aim to analyze the structure of a Local Productive Arrangement (LPA) in the mining sector in one Brazilian Microregion, through the description of their origin, the mapping of productive agents and institutions involved, the explanation of its structure, based on variables related to external economies and internal economies, and identify their stage of evolution. This is a qualitative, descriptive, exploratory and documentary, in the form of case study, which used as a tool for data collection a semi structured interview guide used with the managers of the mining cooperatives. Data were analyzed using the technique of content analysis, under a closed procedure, and document analysis. The main result of the research is that the LPA is in transition from the embryonic stage to growth, once, according to the model adopted in the study, their structure has characteristics of both stages. The study demonstrates to be relevant for treating strategic improvements in the way we manage our business, proposed by forming partnerships between organizations or interorganizational relations of productive cooperation, with an objective to obtain competitive advantages.